Life cycle environmental impacts of cornstalk briquette fuel in China. (15th April 2017) - Wang, Zhiwei; Lei, Tingzhou; Yang, Miao; Li, Zaifeng; Qi, Tian; Xin, Xiaofei; He, Xiaofeng; Ajayebi, Atta; Yan, Xiaoyu
Highlights: First detailed LCA on cornstalk biomass briquette fuel (BBF) in China. Provides up-to-date LCI for cornstalk BBF based on full-scale operational data. Results show cornstalk BBF is more environmentally friendly than coal. Cornstalk BBF is also favourable when compared with other biomass solid fuels. Abstract: The use of agricultural residues to produce biomass briquette fuel (BBF) can reduce waste of resources and consumption of fossil fuels. We report the first detailed environmental impact assessment of cornstalk-based BBF in China using a cradle-to-grave life cycle assessment (LCA). The LCA study was conducted based on a typical large-scale cornstalk BBF demonstration project in China with an integrated and automated production system. The key life cycle stages such as cornstalk growth, cornstalk transportation, BBF production, transportation and utilisation were investigated. Our results suggest that cornstalk BBF in China is much more environmentally friendly than coal and is favourable when compared with other types of solid fuels produced from different biomass feedstock. For example, the climate change and fossil depletion impacts of cornstalk BBF in China (11 g CO2  eq./MJ and 2 g oil eq./MJ, respectively) are an order of magnitude lower than those of coal (146 g CO2  eq./MJ and 26 g oil eq./MJ, respectively). The results of this study can assist policy makers in evaluating the potential benefits of the large scale use of BBF made from agricultural residues.